Cooperative mastery learning strategies and the conventional approach in the teaching of mathematics - Licup, Nora (Education quarterly.)
This study was undertaken to determine the effectiveness of cooperative mastery learning (CML) strategies, as compared to the traditional (large-group and non-mastery) approach in teaching fourth-grade mathematics, in terms of cognitive and affective outcomes.